2021
DOI: 10.1186/s13287-020-02127-2
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30c-5p regulates adventitial progenitor cells differentiation to vascular smooth muscle cells through targeting OPG

Abstract: Background As the most important component of the vascular wall, vascular smooth muscle cells (VSMCs) participate in the pathological process by phenotype transformation or differentiation from stem/progenitor cells. The main purpose of this study was to reveal the role and related molecular mechanism of microRNA-30c-5p (miR-30c-5p) in VSMC differentiation from adventitial progenitor cells expressing stem cell antigen-1(Sca-1). Methods In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…Indeed, OPG upregulation enhanced the expression of the major biomarker of active fibroblasts, a-SMA. Consistent with this, it has been previously shown that OPG positively regulates a-SMA in VSMC [ 28 ]. Likewise, OPG upregulation enhanced the expression of other active fibroblast biomarkers, namely, FAP-a, CD10, GPR77, and CD44.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, OPG upregulation enhanced the expression of the major biomarker of active fibroblasts, a-SMA. Consistent with this, it has been previously shown that OPG positively regulates a-SMA in VSMC [ 28 ]. Likewise, OPG upregulation enhanced the expression of other active fibroblast biomarkers, namely, FAP-a, CD10, GPR77, and CD44.…”
Section: Discussionsupporting
confidence: 85%
“…RT-qPCR was performed as described previously [27] . Briefly, RNA was extracted from the cells using Trizol (12183555, Invitrogen, USA) according to the manufacturer's instructions.…”
Section: Rt-qpcr For Mrna and Mirnamentioning
confidence: 99%
“…Luciferase reporter assays were performed as described in our previous studies [27] . A total of 6×10 4 ESCs were seeded in DM in a collagen-coated 12-well plate.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…Multiple brain conditions, including ischemic stroke and thrombotic vascular events, have been linked to the overexpression of plasminogen activator inhibitor-1 (PAI-1) in the plasma, endothelial cells, and platelets [78]. MiR-30c directly targets the PAI-1 via the SERPINE1 gene [79][80][81] including the osteoprotegerin (OPG) gene [82], which mitigates atherosclerosis, thrombosis, and embolism, which are major causes of clogging of arteries [55]. MiR-30c-5p can protect against endothelial damage by targeting TGF-β1 [83] and TCF21 [58] and attenuating endothelial pyroptosis by downregulating Forkhead Box O3-NOD-, LRR-, and pyrin domain-containing protein 3 (FOXO3-NLRP3) inflammasomes [59] and α2-antiplasmin [84].…”
Section: Mir-30c In Strokementioning
confidence: 99%